Antibiofilm Activity and Biocorrosion Control by Means of Essential Oil from Lippiagracilis Schauer (Verbenaceae) Microemulsion System - Viana, Marcelino Gevilbergue; Lutterbach, Márcia Tereza Soares; Albuquerque, Cynthia Cavalcanti de; da Silva, Djalma Ribeiro; Diniz, Jaécio Carlos; Fernandes Teixeira, Ewerton Richard; do Nascimento Santos, Francisco Josiel; dos Santos, Everaldo Silvino (Journal of Environmental Science and Engineering Technology, 2019)
In this study the use of the essential oil from a Lippiagracilis Schauer micro emulsion system as a biocide and antibiofouling agent upon biofilms as well as the effect of this micro emulsion on the corrosion rate of AISI 1020 carbon steel was investigated. The results showed that a microemulsion type Winsor-IV was efficient in preventing the biofouling formation after 96 hours of contact and inhibited the growth of the sulfate reducing, iron-oxidizing bacteria as well as the fungi forming the biofilms after the 16 days of contact time. The antimicrobial action was likely due to a formation of a protective film.